Эскадра Траяна на Красном море: Евтропий, Дион Кассий и Перипл Эритрейского моря [Alexandr Tcherniak: Trajan’s Fleet on the Red Sea: Eutropius, Cassius Dio and the Periplus Maris Erythraei] - Черняк, А. Б. (Hyperboreus, 2014)
The article discusses the passage of Eutropius about the ﬂeet established by Traian on the Red Sea (Eutr. Brev. 8. 3. 2 In mari Rubro classem instruit, ut per eam Indiae ﬁnes vastaret). The author analyses the evidence of Eutropius and Festus as well as relevant epigraphic material, in the ﬁrst place the recently discovered Roman inscription from the Farasan archipelago dated from AD 144 (AE 2004, no. 1643). The author interprets the sentence from the Periplus Maris Erythraei (PME) 20 that “the Caesar destroyed (or conquered) Adane/Aden” as referring to Traian (ch. 3). Since this interpretation contradicts the commonly accepted dating of the Periplus to AD 70s – 90s, the author reassesses the problem of dating. Apart from the passage on the capture of Aden, the dating of the Periplus depends on the interpretation of the words “to Petra to Malich the king”. The latter is usually believed to be Malich II (AD 60–75); however, it might also have been his homonymous grandson, who was possibly sent by Romans to Petra as ethnarch of Nabateans (AD 114?) and later moved to Hegra. The Malich’s title “the king of Nabateans” (PME) is arguably a later gloss. As a result, the Periplus can be dated between AD 106 and 114. In ch. 5 “Traian and India” the author explains Traian’s attention to India by his interest in Eastern trade, which resulted both in the Parthian war and in the establishing of a ﬂeet on the Red Sea and Indian Ocean. In ch. 6 “Parthians and Saks in the PME”, the author discusses the following questions: 1) the presence of the Parthians in Eastern Arabia; 2) strife of the Parthian princelings in the valley of the Indus (due to the Kushans’ invasion?); 3) the naval policy of the Saks who convoyed all merchant ships to Barigasa. All these circumstances required the presence of the Roman ﬂeet.